NMR Methods for the investigation of structure and transport - Hardy, Edme H. (Springer Berlin Heidelberg, 2012)
Methods of nuclear magnetic resonance (NMR) are increasingly applied in engineering sciences. The book summarizes research in the field of chemical and process engineering performed at the Karlsruhe Institute of Technology (KIT). Fundamentals of the methods are exposed for readers with an engineering background. Applications cover the fields of mechanical process engineering (filtration, solid-liquid separation, powder mixing, rheometry), chemical process engineering (trickle-bed reactor, ceramic sponges), bioprocess engineering (biofilm growth), and food process engineering (microwave heating, emulsions). Magnetic Resonance Imaging (MRI) as well as low-field NMR are covered with notes on hardware. Emphasis is placed on quantitative data analysis and image processing.